Water supply and sanitation in Dhaka City. - Al-Mamun, Abdullah; Noor , M. (2011)
km2 area and provides residence for about 7 Million people. The city is highly potential for the economic and infrastructural development. Similar to other developing regions, this city also lacks many essential needs. Among others, water supply and sanitation are of great concern. Ground water is the main source of potable water supply to the city. Although many rivers passes through the city and the surrounding areas, due to lack of fund, surface water treatment facilities could not be constructed. As such, the city relies on the naturally purified groundwater. The city is served by combination of separate and combined sewer system; again, which is not adequate for the city. Lack of proper operation and maintenance make the sewer system inefficient. Most of the rain events cause localised flooding due to blocked and inadequate sewer systems. The only centralised municipal wastewater treatment facility located at Pagla is unable to cope with the amount of wastewater received by the plant. Although the city is developing rapidly for the housing, roads and industries, the infrastructure facilities related to the water supply and sanitation are not given due attention; mainly due to lack of financial support. As a result, the rivers are heavily polluted due to municipal and industrial waste discharges. Recently, the historical Buriganga River is cleaned by removing the contaminated sediments. However, if proper wastewater treatment infrastructures are not built and operated properly the river water quality will remain unacceptable. This poster paper is intended to draw attention of the international donor agencies to look into the water supply and sanitation status of the most densely populated Mega City of the world. It is realised that there should be proper strategic plan, legislative setup and allocation of adequate fund to properly design, build and operate the facilities related to water supply and sanitation.